DEVELOPMENT OF STRATEGIC ISSUES OF ISLAMIC RELIGIOUS COLLEGE - Fitria Zulfa; Irawan Irawan; Muhammad Zaki Akhbar Hasan; Ahmad Ropei (JURNAL AL-TANZIM, 2021)
This study aims to describe the development of strategic issues at STAI Miftahul Huda Subang based on an analysis of the stages of strategic plan management. This research belongs to the qualitative by using a case study approach (case study). The results showed that the strategic planning of STAI Miftahul Huda was carried out by assessing the strategic issues outlined in the Strategic Plan by conducting various internal and external analyses and relevant to the vision, mission, and goals that had been formulated. Then related to the study of strategic issues, conditions, and directions for the development of STAI, along with the ongoing industrialization process in the Subang area, it becomes an opportunity for institutions to provide the required human resources. In addition, the provision of a digital-based information system to maximize various academic service functions is an essential plan for institutional development, considering that scientific advances, especially in the field of technology and information, are a crucial issue in entering education management in the 4.0 era.